Visible and invisible violence and inequality in neoliberal Santiago. (October 2014) - Rodríguez, Alfredo; Rodríguez, Paula; Saborido, Marisol; Segovia, Olga; Mires, Lylian
This article argues that existing inequalities of all kinds in the city of Santiago de Chile are symptoms of the gap between those who are favoured by the distribution of benefits and those who are at the margins of this process. We propose that these groups are differentiated not only by the socioeconomic sector to which they belong but also by the part of the city in which they live. People's exclusion is also affected by gender. The point of view taken is that although these inequalities have a systemic and structural nature, they are not abstract elements in people's lives. We claim that, in fact, they are social, economic, political and institutional types of violence, which affect individuals and groups. (1) These types of violence, which in turn have visible manifestations (such as direct violence) and invisible manifestations (such as structural and cultural violence), (2) are examined in the case of Santiago de Chile in the context of three different socioeconomic districts (low, medium and high).